ANALISIS KRITIS TENTANG MANAJEMEN DAN KEPEMIMPINAN MUSA BERDASARKAN KELUARAN 18:1:27 - Poluan, Alvonce; Setiawan, Tjutjun; Umboh, Steven Tommy Dalekes (Sekolah Tinggi Teologi Hagiasmos Mission, 2022)
Management and leadership are very important themes in an organization both secular and spiritual, whose goal is to achieve the main target of the organization itself. This study tries to critically analyze Moses' management and leadership based on Exodus 18:1-27. This research uses a qualitative method with a literature study approach, and also through a study of the Bible verses in the eighteenth chapter of Exodus. Through this research, the authors hope that every organization has an understanding of how good management and effective leadership are, so that organizational goals can be achieved. The author concludes that Moses made a change in the pattern of leadership from a